Screening Metagenome for novel N-Hydroxylating Monooxygenases (MMOs) using Bioinformatics and Biotechnological tools - Esuola, Catherine Oluwakemi (North-West University (South Africa), 2016)
Microbial N-hydroxylating monooxygenases (NMOs) are useful industrial biocatalysts that perform the regioselective addition of a single oxygen atom to the terminal amino group of their target substrates (primary aliphatic amines and diamines). These NMOs are particularly sought after industrially as they play a major part in the first step of biosynthesis of metal chelating compounds, siderophores/metallophores. In order to increase available NMOs with novel functional annotations, the microbial metagenome of the TU-GENDB Freiberg, Germany and the National center for Biotechnology Information protein database (NCBI) were screened for novel NMOs with promising and unique functions using some previously known NMOs protein sequences as potential baits. A gene, gorA, encoding for GorA, a putative NMO with functional annotation as a diamine monooxygenase has been discovered from the genome of the Gordonia rubripertincta CWB2. GorA has been cloned and overexpressed in a suitable microbial host Escherichia coli DH5α and Escherichia coli BL21 (DE3) (pLysS) respectively. GorA has been further characterized for its physiological and biochemical properties including its different substrates scope (eleven different substrates, namely ethanolamine, propylamine, N-butylamine; primary chain diamines: 1,3-diaminopropane, 1,4-diaminobutane (putrescine), 1,5-diaminopentane (cadaverine), 1,6-diaminohexane (hexanemethylenediamine), 1,7-diaminoheptane, and 1,8-diaminooctane; amino acids, L-ornithine and L-lysine were assessed. Substrate and co-factor specificity, pH conditions, buffer tests, temperature optimal conditions were evaluated using an appropriate amount of the enzyme and measuring the consumption of nicotinamine adenine dinucleotide phosphate (NADPH) at 340 nm on a spectrophotometer using the standard NADPH oxidation assay. The steady state kinetics of GorA with different concentrations of flavin adenine dinucleotide (FAD) and different concentrations NADPH were assessed spectrophotometrically at 24°C. The kinetic parameters of GorA (1 μM) were assessed spectrophotometrically at 24°C with different concentrations of 1,4-diaminobutane. The hydroxylation assay of GorA (1 μM) were assessed using the Csáky assay at 24°C with different concentrations of 1,4-diaminobutane. The steady state, kinetic parameters, and the hydroxylation assay were fit into the Michealis-Menten constant. The phylogenetic relationship with other known NMOs showed GorA to be grouped with known but yet to be characterized microbial diamine NMO. GorA is thus to the best of our knowledge the first characterized diamine NMO from the genome of the Gordonia rubripertincta CWB2. GorA has an optimal pH range of 7.0-8.0, it is soluble in potassium phosphate buffer, it accepts FAD and NADPH as cofactor and electron donor respectively. GorA is active in the presence of a range of primary diamines, 1,4-diaminobutane > 1,5-diaminopentane > 1,6-diaminohexane > 1,3-diaminopropane > 1,7-diaminoheptane > 1,8-diaminooctane. The activity of GorA in the presence of either of the monoamines or the amino acids was not significant. GorA demonstrated a 100% relative activity in the presence of 1,4-diaminobutane (putrescine) as compared to other substrates tested. The apparent V_max, K_m, and k_cat of the NADPH oxidation is 310 ± 0.01 nmol min-1 mg-1, 361 ± 0.1 μM and 0.27 s^-1 respectively whereas the hydroxylation assay showed GorA with an apparent V_max, K_m and k_cat of 246 ± 0.01 nmol min^-1 mg^-1, 737 ± 0.1 μM, and 0.21 s^-1 respectively. NMOs belongs to the class B monooxygenase family, the other members of this family are the Baeyer-Villiger monooxygenases (BVMOs), the flavin-containing monooxygenases (FMOs) and the class B flavoprotein monooxygenases in plants (YUCCAs). The NMOs have been indicated as the least studied members of these class B monoxygenases, hence in Chapter 2, the known NMOs are reviewed. The most studied members of the class B monooxygenase family are the BVMOs. The NMOs share conserved motif sequence fingerprints with the BVMOs; these allows for their successful identification from the metagenome. The classification and biocatalysis application of BVMOs are reviewed in Chapter 4. NMOs are also implicated as important in diseases causing ability of pathogenic bacteria and fungi, such as DfoA, a putative L-lysine N6-monooxygenase that converts cadaverine into 1-amino-5-(N-hydroxy)-aminopentane, isolated from the enterobacterium Erwinia amylovora, the causative agent of fire blight of pome fruit, and plant growth promoting ability such as PsbA, a pseudobactin A enzyme, that is involved in the first step biosynthesis of pseudobactin from Pseudomonas strain B10. A review of these examples is presented in Chapter 5. This shows the significance of NMOs as novel therapeutic drugs and antibiotics target. Overall, this study has contributed to the available pool of NMOs; particularly, GorA has a biosynthetic role in the production of hydroxamate metallophores for a vibrant and environmentally-safe mobilization of industrially important metals.
PhD (BIology), North-West University, Mafikeng Campus